LINGUISTIC PROBLEMS OF TRANSLATION OF ARTISTIC CENTURIES FROM UZBEK TO ENGLISH AS AN EXAMPLE OF SAID AHMAD'S NOVEL "HORIZON" - Iroda Jurayeva Ahmedovna (Western European Studies, 2024)
This article analyzes several punctuational and lexicological transformations that took place in the process of translating one of the masterpieces of Uzbek literature "Horizon" from Uzbek to English
Keywords: translation; literary translation; lexicological transformations